Degradable bio-based system for sand consolidation and profile control, preparation method and application thereof
By adopting a degradable bio-based system and using cross-linking reaction to form a high-strength and flexible bio-based thermosetting material, the problems of low compressive strength and difficult degradation of the solid body in the prior art are solved, and effective sand solidification and reservoir profile adjustment in oil fields are achieved.
Patent Information
- Application Number
- CN202411700611.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Among the existing chemical sand solidification technology, the compressive strength of the epoxy resin system after consolidation is low and is not easy to degrade, which cannot effectively solve the problems of well sand output and reservoir profile adjustment.
A bio-based thermosetting material with high strength and flexibility is formed by cross-linking reaction, including 1,4:3,6-di-dehydration-D-sorbitol/maleic anhydride binary copolymer, resin, glycol dimethyl ether, toughening agent and curing agent, and degradation in an alkaline environment.
The consolidation strength reaches 4.2MPa and is completely degraded in a 50°C aqueous NaOH solution, which solves the problems of low compressive strength and difficult degradation of the consolidated body in the prior art, and has good sand-fixing and profiling properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a degradable bio-based system for sand consolidation and profile control, and a preparation method and application thereof. Background Art
[0002] As the development time of oil fields increases, the problem of sand production in water wells becomes more and more serious. At present, mechanical sand control has poor sand control effect on fine silt, and can only block sand but not consolidate sand, which cannot fundamentally solve the problem of sand production in reservoirs. Therefore, chemical sand control has gradually become the mainstream. Among them, epoxy resin is increasingly widely used in chemical sand consolidation systems due to its excellent curing performance and mechanical properties. However, epoxy resin materials are difficult to degrade and reuse after curing, leading to environmental pollution and waste of resources. This also limits the promotion and application of such non-degradable resin materials.
[0003] In recent years, bio-based epoxy resins have become increasingly popular. Bio-based epoxy resins have many advantages such as environmental friendliness, low cost, and wide sources. In order to solve the problem of epoxy resin system pollution to the formation environment in chemical sand consolidation, the use of bio-based epoxy resins will become a top priority.
[0004] The Chinese invention patent with application number 202210265118.1 discloses a biodegradable bio-based resin water plugging agent suitable for medium and low temperature oil reservoirs and its application. The biodegradable bio-based resin water plugging agent comprises the following components: 82.4-90.6 parts of base liquid, 5.6-12.0 parts of curing agent, 0.1-3 parts of initiator, and 1.5-2.2 parts of reinforcing agent, wherein the base liquid is epoxidized sucrose soybean oleate. The modified soybean oil in the biodegradable bio-based resin water plugging agent contains a large number of epoxy groups. In the oil reservoir temperature environment of 50-120°C, the epoxy groups open under the action of the initiator, and then associate with the curing agent to form a macromolecule with a network structure. The reinforcing agent with a rigid group is introduced to further improve the hardness of the resin network structure, and a volatile organic compound-free, high-performance, all-biobased thermosetting resin is prepared. The biodegradable bio-based resin water plugging agent has high strength, strong anti-dilution ability, and excellent long-term stability. At 80°C, the compressive strength of the resin is greater than 60MPa, and the mass retention rate after aging for 60 days is greater than 95%. However, the system cannot be used for chemical sand consolidation, and the degradation time of the system is too long.
[0005] The Chinese invention patent with application number 202010587148.5 discloses a bio-based recyclable thermosetting resin and a preparation method thereof, and the specific steps are as follows: (1) using vanillin monomer as raw material to prepare a multi-aldehyde bio-based resin; (2) dissolving the bio-based resin containing multi-functional aldehyde groups in an organic solvent, adding amine monomers, stirring evenly, removing the solvent, and hot pressing to obtain a bio-based recyclable thermosetting resin. The raw materials used in the present invention are all bio-based sources, which is in line with sustainable development. The polymer is prepared by the Schiff base reaction of aldehyde and amino groups, which has high reaction activity, simple operation, and high yield. The obtained bio-based polymer has good thermal stability, recyclability and degradability. However, if the bio-based resin described in the patent is used for chemical sand consolidation, there is a problem of low compressive strength of the consolidated body after consolidating the sand particles, and a good consolidation effect of the sand particles cannot be achieved. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a degradable bio-based system for sand consolidation and profile control, and a preparation method and application thereof.
[0007] The present invention is achieved through the following technical solutions:
[0008] A degradable bio-based system for sand consolidation and profile control comprises, based on 100 parts by total weight, 15-25 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, 30-40 parts of resin, 10-15 parts of ethylene glycol dimethyl ether, 5-8 parts of toughening agent, 10-12 parts of curing agent, and the balance being water.
[0009] The above-mentioned biodegradable bio-based system, based on 100 parts by total weight, includes: 18-22 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, 33-36 parts of resin, 10-12 parts of ethylene glycol dimethyl ether, 6-7 parts of toughening agent, 10-12 parts of curing agent, and the balance is water.
[0010] The above-mentioned biodegradable bio-based system, based on a total weight of 100 parts, includes: 20 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer, 35 parts of resin, 10 parts of ethylene glycol dimethyl ether, 6 parts of polyurethane acrylate, 12 parts of triethylenetetramine, and the balance is water.
[0011] In the above-mentioned biodegradable bio-based system, the 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is prepared by the following method:
[0012] (1) maleic anhydride and 1,4:3,6-dianhydro-D-sorbitol are mixed in a weight ratio of 1.8-2.2:(0.9-1.1), heated at 100-110°C, and stirred for 5-6 hours;
[0013] (2) After the reaction is completed, the binary copolymer is obtained by washing and drying.
[0014] The above-mentioned biodegradable bio-based system, the resin includes castor oil, glycidyl ether epoxy resin and epoxidized soybean oil.
[0015] In the above-mentioned biodegradable bio-based system, the weight ratio of the castor oil, the glycidyl ether epoxy resin and the epoxidized soybean oil is (0.8-1): (1.9-2.1): (2.9-3.2).
[0016] In the above-mentioned biodegradable bio-based system, the weight ratio of the castor oil, the glycidyl ether epoxy resin and the epoxidized soybean oil is 1:2:3.
[0017] In the above-mentioned biodegradable bio-based system, the toughening agent comprises polyurethane acrylate.
[0018] In the above-mentioned biodegradable bio-based system, the curing agent includes one or more of triethylenetetramine and diethylenetriamine.
[0019] On the other hand, the present invention also provides a method for preparing the above-mentioned degradable bio-based system, comprising:
[0020] (1) mixing the resin and 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer in a solvent consisting of ethylene glycol dimethyl ether and deionized water in a certain proportion and stirring the mixture uniformly;
[0021] (2) Add toughening agent in proportion and mix well;
[0022] (3) Add the curing agent in proportion and mix and stir evenly to obtain a degradable bio-based system.
[0023] In another aspect, the present invention further provides the use of the above-mentioned degradable bio-based system or the degradable bio-based system prepared by the above-mentioned preparation method in sand consolidation and profile control in oil fields.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The biodegradable bio-based system for sand consolidation and profile control provided by the present invention not only has good sand consolidation performance and can solve the problem of sand production in water wells, but also has a certain effect of blocking high permeability layers and adjusting the reservoir profile near water injection wells, and has both water well sand consolidation and profile control functions;
[0026] (2) The biodegradable bio-based system for sand consolidation and profile control provided by the present invention also solves the technical problems of low compressive strength and difficulty in degradation of the consolidated body after sand consolidation in the existing chemical sand consolidation technology;
[0027] (3) The degradable bio-based system for sand consolidation and profile control provided by the present invention has a consolidation strength of up to 4.2 MPa, and can be degraded and completely dissolved in a 50°C NaOH aqueous solution, showing excellent degradation ability. DETAILED DESCRIPTION
[0028] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.
[0029] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0030] In a first aspect, the present invention provides a degradable bio-based system for sand consolidation and profile control, comprising: 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, resin, ethylene glycol dimethyl ether, a toughening agent, a curing agent, and water.
[0031] The present invention prepares a carboxylic acid functional dimer by reacting 1,4:3,6-dianhydro-D-sorbitol with maleic anhydride, and can crosslink castor oil, glycidyl ether epoxy resin and epoxy soybean oil under the action of water and ethylene glycol dimethyl ether to obtain a bio-based degradable thermosetting material with both strength and flexibility. The addition of toughening agent polyurethane acrylate can greatly improve the flexibility of the system, and contains a large number of acrylic functional groups and carbamate bonds, which can be destroyed in an alkaline environment. In the degradable bio-based system of the present invention, the components have a synergistic effect to make their consolidation strength reach 4.2MPa, and can be degraded and completely dissolved in a 50°C NaOH aqueous solution, showing excellent degradation ability.
[0032] The components of the biodegradable bio-based system for sand consolidation and profile control of the present invention are described in detail below:
[0033] 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer
[0034] 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is the crosslinker of the system. At the same time, the introduction of rigid isosorbide structure gives the system network hardness, and its potential conformational transition can maintain or even improve the flexibility of the resin network.
[0035] In some preferred embodiments, the 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is prepared by the following method: (1) maleic anhydride and 1,4:3,6-dianhydro-D-sorbitol are mixed in a weight ratio of (1.8-2.2): (0.9-1.1), heated at 100-110° C., and stirred for 5-6 hours; (2) after the reaction is completed, the binary copolymer is obtained by washing and drying.
[0036] In the biodegradable bio-based system of the present invention, the proportion of the 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is 15-25 parts based on 100 parts by total weight.
[0037] According to practice, when the ratio of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is less than the above range, maleic anhydride cannot be completely reacted regardless of whether the reaction time is extended or the reaction temperature is adjusted. When the ratio of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is too large or too small, the yield will be reduced.
[0038] In some preferred embodiments, based on 100 parts by total weight, the proportion of the 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is 18-22 parts.
[0039] More preferably, based on 100 parts by total weight, the proportion of the 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is 20 parts.
[0040] Resin
[0041] The resin has excellent mechanical properties after curing and is used to improve the mechanical properties of the overall cured product.
[0042] In some preferred embodiments, the resin is a compound including castor oil, glycidyl ether epoxy resin and epoxidized soybean oil.
[0043] Among them, glycidyl ether epoxy resin is less brittle, tough, not easy to crack, and does not shrink, deform, and has strength after curing. As a main body, it is a skeleton material with excellent mechanical properties and adhesive properties. Castor oil, epoxidized soybean oil and glycidyl ether epoxy resin cross-link 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer under the action of water and ethylene glycol dimethyl ether to obtain a bio-based degradable thermosetting material with both strength and flexibility.
[0044] In some preferred embodiments, the weight ratio of the castor oil, the glycidyl ether epoxy resin and the epoxidized soybean oil is (0.8-1): (1.9-2.1): (2.9-3.2).
[0045] Further preferably, the weight ratio of the castor oil, the glycidyl ether epoxy resin and the epoxidized soybean oil is 1:2:3.
[0046] In some preferred embodiments, the proportion of the resin in the degradable bio-based system is 30-40 parts based on 100 parts of the total weight.
[0047] In practice, when the resin ratio is less than the above range, the overall curing strength of the system is low; when the resin ratio is greater than the above range, the degradation effect becomes worse due to the smaller proportion of the cross-linking agent.
[0048] In some preferred embodiments, based on 100 parts by total weight, the resin is present in an amount of 33-36 parts.
[0049] Further preferably, based on 100 parts by total weight, the resin is present in an amount of 35 parts.
[0050] Ethylene glycol dimethyl ether
[0051] Ethylene glycol dimethyl ether is used as a solvent to dissolve the resin so as to react smoothly with the binary polymer.
[0052] In some preferred embodiments, based on 100 parts by total weight, the proportion of ethylene glycol dimethyl ether in the degradable bio-based system is 10-15 parts.
[0053] According to practice, when the proportion of ethylene glycol dimethyl ether is less than the above range, the resin is not fully dissolved; when the proportion of ethylene glycol dimethyl ether is greater than the above range, the cost is increased, which is not economical.
[0054] In some preferred embodiments, based on 100 parts by total weight, the proportion of ethylene glycol dimethyl ether is 10-12 parts.
[0055] Further preferably, based on 100 parts by total weight, the proportion of ethylene glycol dimethyl ether is 10 parts.
[0056] Toughening agent
[0057] Toughening agents are used to increase the compressive strength of the system and prevent the cured product from breaking directly due to extrusion.
[0058] In some preferred embodiments, the toughening agent includes polyurethane acrylate, wherein polyurethane acrylate has the advantages of good toughening effect and no reaction with components in the system.
[0059] In some preferred embodiments, the proportion of the toughening agent in the degradable bio-based system is 5-8 parts based on 100 parts of the total weight.
[0060] According to practice, when the ratio of the toughening agent is less than the above range, the toughening effect is not obvious; when the ratio of the toughening agent is greater than the above range, the cost is increased, which is not economical.
[0061] In some preferred embodiments, the toughening agent is present in an amount of 6-7 parts based on 100 parts by total weight.
[0062] Further preferably, based on 100 parts by total weight, the toughening agent is present in an amount of 6 parts.
[0063] Curing agent
[0064] Curing agents are used to cure the resin.
[0065] In some preferred embodiments, the curing agent includes: one or more of triethylenetetramine and diethylenetriamine.
[0066] The curing agent used in the present invention has more amine groups and its alkalinity is within the acceptable range of the system.
[0067] In some preferred embodiments, the proportion of the curing agent in the degradable bio-based system is 10-12 parts based on 100 parts of the total weight.
[0068] In practice, when the ratio of the curing agent is less than the above range, the reaction is not sufficient; when the ratio of the curing agent is greater than the above range, the cost is increased, which is not economical.
[0069] Further preferably, based on 100 parts by total weight, the curing agent is mixed in a ratio of 12 parts.
[0070] In a second aspect, the present invention also provides a method for preparing the above-mentioned degradable bio-based system, comprising:
[0071] (1) mixing the resin and 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer in a solvent consisting of ethylene glycol dimethyl ether and deionized water in a certain proportion and stirring the mixture uniformly;
[0072] (2) Add toughening agent in proportion and mix well;
[0073] (3) Add the curing agent in proportion and mix and stir evenly to obtain a degradable bio-based system.
[0074] The types, proportions and functions of raw materials involved in the preparation method are the same as those in the degradable bio-based system provided in the first aspect of the present invention, and the present invention will not repeat them here.
[0075] In some preferred embodiments, the method for preparing the degradable bio-based system of the present invention comprises:
[0076] (1) Compounding castor oil, glycidyl ether epoxy resin, and epoxy soybean oil in a weight ratio of 1:2:3 to obtain a resin;
[0077] (2) 35 parts of the resin and 20 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer are dissolved in a solvent consisting of 10 parts of ethylene glycol dimethyl ether and 17 parts of deionized water;
[0078] (3) Add 6 parts of polyurethane acrylate and mix well;
[0079] (3) Add 12 parts of triethylenetetramine in proportion and stir evenly to obtain a degradable bio-based system.
[0080] The biodegradable bio-based system prepared by the method of the present invention comprises castor oil, epoxy glycidyl ether resin and epoxy soybean oil. After curing, the epoxy glycidyl ether resin is less brittle, tough, not easy to crack, does not shrink, does not deform, and has strength. As a main body, it is a skeleton material with excellent mechanical properties and adhesive properties. The 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer cross-links castor oil, epoxy soybean oil and epoxy glycidyl ether resin under the action of water and ethylene glycol dimethyl ether to obtain a bio-based biodegradable thermosetting material with both strength and flexibility. Since both ends of the epoxy resin matrix molecular chain have epoxy groups, they can undergo cross-linking reactions with amines and anhydride compounds containing active hydrogen to form a dense three-dimensional network structure, so that the solid body has a certain strength. The addition of the curing agent triethylenetetramine allows the cross-linking reaction to proceed further, forming more three-dimensional network structures, thereby improving the strength of the solid body. The 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer has high acidity due to the combination of carbon-carbon double bonds, and the system contains a large number of acrylic functional groups and carbamate bonds, which can be destroyed in an alkaline environment. Therefore, it is destroyed by a large number of functional groups in the NaOH aqueous solution, and the system gradually decomposes and dissolves in the solution.
[0081] In a third aspect, the present invention also provides the application of a degradable bio-based system in sand consolidation and profile control in oil fields.
[0082] Example
[0083] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods without specific conditions in the following examples are based on conventional methods and conditions.
[0084] The sources of the raw materials used in the following examples are as follows:
[0085] Castor oil: industrial grade, Fucheng County Huanyu Oil Co., Ltd.;
[0086] Glycidyl ether epoxy resin: industrial grade, Kunshan Jiulimei Electronic Materials Co., Ltd., product number: E51;
[0087] Cyclopropoxy soybean oil: AR grade, Shanghai MacLean Biochemical Technology Co., Ltd.;
[0088] Triethylenetetramine: AR grade, Shanghai Myril Biochemical Technology Co., Ltd.;
[0089] Polyurethane acrylate: AR grade, Ruisheng New Materials Co., Ltd., product number: Sartomer CN2203 NS.
[0090] The preparation method of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary polymer is as follows: maleic anhydride and isosorbide are placed in a bottle at a mass ratio of 2:1, stirred magnetically, heated to 105°C, and kept at 105°C for 5 hours. Then, the mixture is washed twice with a mixture of ethyl acetate and petroleum ether (1:1); after washing with ethyl acetate, it is dried in a vacuum oven at 100°C for 5 hours to obtain a binary copolymer.
[0091] The resin is obtained by compounding castor oil, glycidyl ether epoxy resin and epoxy soybean oil in a weight ratio of 1:2:3.
[0092] Example 1
[0093] Mix 27 parts of water and 10 parts of ethylene glycol dimethyl ether evenly, then add 30 parts of resin and 15 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer, and stir; finally, add 6 parts of polyurethane acrylate and 12 parts of triethylenetetramine in sequence, mix and stir evenly to obtain a degradable bio-based system for sand consolidation and profile control.
[0094] The system was divided into two groups, mixed with quartz sand respectively, aged at 50°C, and the compressive strength was measured. Then the consolidated body was placed in a 0.01 mol / L NaOH aqueous solution to observe the change of compressive strength over time. The results are shown in Table 1.
[0095] Table 1 Compressive strength changes over time
[0096]
[0097] Example 2
[0098] Mix 15 parts of water and 12 parts of ethylene glycol dimethyl ether evenly, then add 35 parts of resin and 20 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer, and stir; finally, add 6 parts of polyurethane acrylate and 12 parts of triethylenetetramine in sequence, mix and stir evenly to obtain a degradable bio-based system for sand consolidation and profile control.
[0099] The system was divided into two groups, mixed with quartz sand respectively, aged at 50°C, and the compressive strength was measured. Then the consolidated body was placed in a 0.01 mol / L NaOH aqueous solution to observe the change of compressive strength over time. The results are shown in Table 2.
[0100] Table 2 Compressive strength changes over time
[0101]
[0102] Example 3
[0103] Mix 2 parts of water and 15 parts of ethylene glycol dimethyl ether evenly, then add 40 parts of resin and 25 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, and stir; finally, add 6 parts of polyurethane acrylate and 12 parts of triethylenetetramine in sequence, mix and stir evenly to obtain a degradable bio-based system for sand consolidation and profile control.
[0104] The system was divided into two groups, mixed with quartz sand respectively, aged at 50°C, and the compressive strength was measured. Then the consolidated body was placed in a 0.01 mol / L NaOH aqueous solution to observe the change of compressive strength over time. The results are shown in Table 3.
[0105] Table 3 Compressive strength changes over time
[0106]
[0107] Comparative Example 1
[0108] First, 40 parts of water and 12 parts of ethylene glycol dimethyl ether are mixed evenly, then 20 parts of resin and 10 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer are added and mixed, and finally 6 parts of polyurethane acrylate and 12 parts of triethylenetetramine are added and stirred evenly to obtain a degradable bio-based system for sand consolidation and profile control.
[0109] The system was divided into two groups, mixed with quartz sand respectively, aged at 50°C, and the compressive strength was measured. Then the consolidated body was placed in a 0.01 mol / L NaOH aqueous solution to observe the change of compressive strength over time. The results are shown in Table 4.
[0110] Table 4 Compressive strength changes over time
[0111]
[0112] Comparative Example 2
[0113] 20 parts of glycidyl ether epoxy resin, 35 parts of triethylenetetramine and the balance of water, the sum of the weight parts of the above components being 100, are mixed and stirred evenly to obtain a resin system for sand consolidation.
[0114] The system was divided into two groups, mixed with quartz sand respectively, aged at 50°C, and the compressive strength was measured. Then the consolidated body was placed in a 0.01 mol / L NaOH aqueous solution to observe the change of compressive strength over time. The results are shown in Table 5.
[0115] Table 5 Compressive strength changes over time
[0116]
[0117] It can be seen from Tables 1 to 5 that the compressive strength of common sand consolidation resin systems weakens as alkalization proceeds, but it is not enough to cause degradation. The bio-based degradable thermosetting material obtained by using 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, castor oil, glycidyl ether epoxy resin and epoxy soybean oil. As the alkalization proceeds, the compressive strength weakens until most of the functional groups are destroyed and degradation occurs. When the main content is too little, the compressive strength is low. As the main content increases, the compressive strength gradually increases, but the degradation is completed within 120 minutes.
[0118] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.
Claims
1. A degradable bio-based system for sand consolidation and profile control, characterized in that: Based on the total weight of 100 parts, it includes: 15-25 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, 30-40 parts of resin, 10-15 parts of ethylene glycol dimethyl ether, 5-8 parts of toughening agent, 10-12 parts of curing agent, and the balance is water; The resin includes castor oil, glycidyl ether epoxy resin and epoxy soybean oil; the toughening agent includes polyurethane acrylate; the curing agent includes one or more of triethylenetetramine and diethylenetriamine; Wherein, the weight ratio of the castor oil, the glycidyl ether epoxy resin and the epoxy soybean oil is (0.8-1): (1.9-2.1): (2.9-3.2).
2. The degradable bio-based system according to claim 1, characterized in that: Based on 100 parts by total weight, the composition comprises: 18-22 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, 33-36 parts of resin, 10-12 parts of ethylene glycol dimethyl ether, 6-7 parts of toughening agent, 10-12 parts of curing agent, and the balance is water.
3. The degradable bio-based system according to claim 1, characterized in that: The total weight is 100 parts, including: 20 parts of 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer, 35 parts of resin, 10 parts of ethylene glycol dimethyl ether, 6 parts of polyurethane acrylate, 12 parts of triethylenetetramine, and the balance is water.
4. The degradable bio-based system according to claim 1, characterized in that: The 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride binary copolymer is prepared by the following method: (1) maleic anhydride and 1,4:3,6-dianhydro-D-sorbitol are mixed in a weight ratio of 1.8-2.2:(0.9-1.1), heated at 100-110°C, and stirred for 5-6 hours; (2) After the reaction is completed, the binary copolymer is obtained by washing and drying.
5. The degradable bio-based system according to claim 1, characterized in that: The weight ratio of the castor oil, the glycidyl ether epoxy resin and the epoxidized soybean oil is 1:2:
3.
6. The method for preparing a degradable bio-based system according to any one of claims 1 to 5, characterized in that: include: (1) mixing the resin and 1,4:3,6-dianhydro-D-sorbitol / maleic anhydride copolymer in a solvent consisting of ethylene glycol dimethyl ether and deionized water in a certain proportion and stirring the mixture uniformly; (2) Add toughening agent in proportion and mix well; (3) Add the curing agent in proportion and mix and stir evenly to obtain a degradable bio-based system.
7. Use of the degradable bio-based system according to any one of claims 1 to 5 or the degradable bio-based system prepared by the preparation method according to claim 6 in sand consolidation and profile control in oil fields.
Citation Information
Patent Citations
Bio-based recyclable thermosetting resin
CN111620992A
Degradable bio-based resin water shutoff agent suitable for medium and low temperature oil reservoirs and application thereof
CN116804144A
Toughened thermosetting epoxy resin composition and preparation method thereof
CN105504692A
Hydraulic fracturing proppant as well as preparation method and application thereof
CN110982510A